2020
DOI: 10.46223/hcmcoujs.econ.en.10.1.216.2020
|View full text |Cite
|
Sign up to set email alerts
|

Lecturers' adoption to use the online Learning Management System (LMS): Empirical evidence from TAM2 model for Vietnam

Abstract: Online training has been a common form of training all over the world for many years ago; however, it is only a side choice alongside offline training. Not only students but also lecturers prefer offline training to online training. However, in some cases of force majeure, specifically the nCov-19 flu pandemic, online training is considered the best way to teach. This study is based on the Technology Acceptance Model 2 (TAM2) to learn about the lecturers' adoption of using the learning management system (LMS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 19 publications
(28 reference statements)
2
18
1
Order By: Relevance
“…If the taxpayers think that e-Local Tax Return can do its task well, then it can increase their trust that e-Local Tax Return has usefulness. Previous research conducted by Khoa et al (2020) found that output quality has a positive effect on perceived usefulness, while research by Ebnehoseini et al (2020) and Primasari et al (2017) found that output quality has not to effect on perceived usefulness. H1 : Subjective norm gives a positive effect on perceived usefulness.…”
Section: Subjective Norm and Output Qualitymentioning
confidence: 85%
See 4 more Smart Citations
“…If the taxpayers think that e-Local Tax Return can do its task well, then it can increase their trust that e-Local Tax Return has usefulness. Previous research conducted by Khoa et al (2020) found that output quality has a positive effect on perceived usefulness, while research by Ebnehoseini et al (2020) and Primasari et al (2017) found that output quality has not to effect on perceived usefulness. H1 : Subjective norm gives a positive effect on perceived usefulness.…”
Section: Subjective Norm and Output Qualitymentioning
confidence: 85%
“…The intention to continue using electronic applications is directly by the perceived usefulness and satisfaction, and then the satisfaction was affected by the confirmation and perceived usefulness, while the confirmation affects the perceived usefulness (Kholid et al, 2018). When there is the assurance of the easy use of the system, it can increase the trust that the system has usefulness (Aji et al, 2020;Bhattarai & Maharjan, 2020;Choi & Park, 2020;Khoa et al, 2020;Primasari et al, 2017;Rana & Dwivedi, 2015;Roy, 2017;Sumardi & Andreani, 2021;Usman et al, 2020). This study supposes that e-Local Tax Return is easily used to increase the assurance that e-Local Tax Return has usefulness, as it can increase efficiency, effectivity, and work productivity because the tax reporting can be conducted anywhere/everywhere.…”
Section: Perceived Ease Of Usementioning
confidence: 95%
See 3 more Smart Citations